2014
DOI: 10.1186/1471-2334-14-490
|View full text |Cite
|
Sign up to set email alerts
|

Rural-to-urban migrants are at high risk of sexually transmitted and viral hepatitis infections in China: a systematic review and meta-analysis

Abstract: BackgroundRapid economic development in urban China has led to a mass migration of surplus rural residents into urban areas for better employment opportunities. This study aims to identify prevalence levels and risks of sexually transmitted infections (STIs) and hepatitis among the rural-to-urban migrant population in China.MethodsChinese and English literature databases were searched for studies reporting prevalence of HIV, STIs and viral hepatitis among rural-to-urban migrants in China between 1990 and 2013.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
60
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 51 publications
7
60
2
Order By: Relevance
“…In this study most of patients with good social-economic status were residing in urban hence at higher risk of sexual behaviours in seeking good life. This is further supported by previous study which reported that migration from rural to urban for seeking good life was significantly found to be associated with STIs infection among women [19].…”
Section: Discussionsupporting
confidence: 79%
“…In this study most of patients with good social-economic status were residing in urban hence at higher risk of sexual behaviours in seeking good life. This is further supported by previous study which reported that migration from rural to urban for seeking good life was significantly found to be associated with STIs infection among women [19].…”
Section: Discussionsupporting
confidence: 79%
“…3 This indicates a six-and four-fold higher risk of HIV infection than in the general Chinese population (0.06%) and pregnant women (0.10%), respectively. 4,52 The HIV disease burden in FSWs in China is much lower than the corresponding levels in low-and middle-income country settings. 27,53 The overall stabilizing trend may effectively be a result of the drastic scale-up of condom programmes and increased access to HIV testing and counselling services for Chinese FSWs.…”
Section: Discussionmentioning
confidence: 98%
“…For people born in compliance with the one-child policy after 1980, it is likely that they have to care for two parents and four grandparents by themselves. The speedy economic growth in China over these years is rapidly inducing a series of socioeconomic changes, including the over 200 million rural-to-urban migrants who move to and temporarily live in cities with the intention to grasp better employment opportunities (Zou et al, 2014). This urban migration combined with an expanding trend in young couples of living separately from their parents, giving rise to the ‘empty nest’ phenomenon, is common not only in rural areas but also in urban cities, with a prevalence rate of 31.8% in 2010 (Liu et al, 2015; Liu and Guo, 2008; Zou et al, 2014).…”
Section: Health Challenges In the Chinese Elderlymentioning
confidence: 99%
“…The speedy economic growth in China over these years is rapidly inducing a series of socioeconomic changes, including the over 200 million rural-to-urban migrants who move to and temporarily live in cities with the intention to grasp better employment opportunities (Zou et al, 2014). This urban migration combined with an expanding trend in young couples of living separately from their parents, giving rise to the ‘empty nest’ phenomenon, is common not only in rural areas but also in urban cities, with a prevalence rate of 31.8% in 2010 (Liu et al, 2015; Liu and Guo, 2008; Zou et al, 2014). The ‘empty nest’ is negatively associated with life satisfaction, and ‘empty nest’ elders manifest a higher incidence of depression and loneliness, and have an urgent need for geriatric care services, especially home care (Liu et al, 2015; Liu and Guo, 2008).…”
Section: Health Challenges In the Chinese Elderlymentioning
confidence: 99%